Strategy for Establishment Santri Leadership Character - Aldo Redho Syam; Nurul Ulfatin; Maisyaroh Maisyaroh (Postgraduate Program Magister Pendidikan Agama Islam, 2020)
The purpose of this study was to describe the Strategic Forming of Santri Leadership Character in Islamic Boarding Schools. This research uses a qualitative approach. Data collected by interview and observation methods. The location of the study was Pondok Modern Darussalam Gontor. As for the results of his research are as follows: (1) In shaping the character of leadership of students, Islamic boarding schools have a purpose that is directed, as for the objectives are: a) students are able to form leadership characters in themselves; b) students are able to be confident in their abilities and potential; c) students are able to have a directed mindset in choosing their life goals; and d) students are able to build dynamic attitudes and behavior; (2) Care of students as an extension of the leadership of Islamic boarding schools and leaders in student activities for 24 hours, has been able to design strategies in shaping the character of student leadership with the following steps, direction; training; assignment; refraction; and escort; and (3) In addition to making steps in shaping the character of santri leadership, the nurturing of santri has also set benchmarks of success in the process of shaping the character of santri leadership, namely: testing with problems; test to make a choice; test to be ready to sacrifice; test to be firm in attitude; and test to evaluate yourself.Tujuan penelitian ini untuk mendeskripsikan strategi pembentukan karakter kepemimpinan santri di pondok pesantren. Penelitian ini menggunakan pendekatan kualitatif. Data dikumpulkan dengan metode wawancara, dan observasi. Lokasi penelitian adalah Pondok Modern Darussalam Gontor. Adapun hasil penelitiannya adalah: (1) Dalam membentuk karakter kepemimpinan santri, Pondok Pesantren telah memiliki tujuan yang terarah, adapun tujuanya adalah: a) santri mampu membentuk karakter kepemimpinan dalam dirinya sendiri; b) santri mampu percaya diri terhadap kemampuan dan potensi dirinya; c) santri mampu memiliki pola pikir terarah dalam memilih tujuan hidup mereka; dan d) santri mampu membangun sikap dan tingkah laku yang dinamis; (2) Pengasuhan santri sebagai kepanjangan tangan dari pimpinan pondok pesantren dan pemimpin dalam aktifitas santri selama 24 jam, telah mampu merancang strategi dalam pembentukan karakter kepemimpinan santri dengan langkah-langkah sebagai berikut, pengarahan; pelatihan; penugasan; pembiasan; dan pengawalan; dan (3) Selain membuat langkah-langkah dalam pembentukan karakter kepemimpinan santri, pengasuhan santri juga telah menetapkan tolak ukur keberhasilan dalam proses pembentukan karakter kepemimpinan santri, yaitu: menguji dengan permasalahan; menguji untuk memutuskan pilihan; menguji untuk siap berkorban; menguji untuk tegas dalam bersikap; dan menguji untuk mengevaluasi diri sendiri.